Long‐term outcomes of endoscopic double stenting using an anti‐reflux metal stent for combined malignant biliary and duodenal obstruction. (30th May 2022) - Sasaki, Takashi; Takeda, Tsuyoshi; Yamada, Yuto; Okamoto, Takeshi; Mori, Chinatsu; Mie, Takafumi; Kasuga, Akiyoshi; Matsuyama, Masato; Ozaka, Masato; Sasahira, Naoki
Abstract: Purpose: To evaluate long‐term outcomes of endoscopic double stenting using anti‐reflux metal stents (ARMS) for combined malignant biliary and duodenal obstruction. Methods: Consecutive patients with advanced pancreatic cancer who received endoscopic double stenting with self‐expandable metal stents (SEMS) for combined malignant biliary and duodenal obstruction at our institution between July 2014 and March 2021 were evaluated. Patients were divided into the ARMS group, endoscopic ultrasound‐guided hepaticogastrostomy (EUS‐HGS) group, and covered metal stent‐transpapillary (CMS‐transpapillary) group. A Duckbill‐type metal stent was used in all ARMS cases. Results: Thirty‐eight patients were enrolled: ARMS group (n = 16), EUS‐HGS group (n = 13), and CMS‐transpapillary group (n = 9). Overall survival among three groups were not significantly different. Recurrent biliary obstruction (RBO) rates of the ARMS, EUS‐HGS, and CMS‐transpapillary groups were 12.5%, 61.5%, and 88.9% ( P  < .01) and median time to recurrent biliary obstructions (TRBOs) were not reached, 125 days, and 7 days ( P  < .01). Median TRBOs of ARMS‐choledochoduodenostomy and ARMS‐transpapillary were not statistically different. Major causes of RBO were stent occlusion and symptomatic stent migration in the ARMS group, hyperplasia in the EUS‐HGS group, and non‐occlusion cholangitis in the CMS‐transpapillary group. Conclusions: Endoscopic double stenting with ARMS might be an option for combined malignant biliary and duodenal obstruction. Abstract : Sasaki and colleagues report the potential benefits of transpapillary biliary stenting or endoscopic ultrasound‐guided choledochoduodenostomy using an anti‐reflux metal stent for combined malignant biliary and duodenal obstruction compared with endoscopic ultrasound‐guided hepaticogastrostomy using a partially‐covered stent and transpapillary biliary stenting using a conventional fully‐covered metal stent.